Integration of AHP and SAW Methods for Disaster Evacuation Location Selection in Cimahi City - Shabrina, Fitriana Nur; Syafrianita, Syafrianita; Lestiani, Melia Eka (Sainteks: Jurnal Sain dan Teknik, 2025)
This study was conducted in Cimahi City, West Java Province, and aims to determine suitable evacuation sites by identifying relevant criteria, evaluating existing sites, selecting the most appropriate locations, and assessing vehicle compatibility for emergency access. The research used the AHP and SAW methods. Data were collected through Focus Group Discussions, questionnaires, and field observations. The study identified four main criteria and eleven sub-criteria: land use: land ownership, land area, and land suitability; accessibility: proximity to evacuation routes and road networks; infrastructure availability: proximity to the cimahi bpbd office, security facilities, medical facilities, and clean water facilities; and environmental factors: secondary hazards and pollution sources. The results showed that the most suitable evacuation sites based on the combined weight of sub-criteria are: Alun-Alun Cimahi (Cimahi Tengah), Lapangan Dapenma Pamsi (Cimahi Selatan), Lapangan Arhanud (Cimahi Tengah), Lapangan Manunggal Brigif (Cimahi Selatan), Lapangan Bola P4TK BMTI/TTUC (Cimahi Utara), and Lapangan Cibaligo (Cimahi Utara). All evacuation sites can be accessed by all types of vehicles owned by the Cimahi City BPBD, such as ranger cars, trail motorcycles, water tank trailers, pickup trucks, and field kitchen trucks.